PENGARUH INTERVENSI ORANG TUA TERHADAP KEBERLANGSUNGAN RUMAH TANGGA ANAK - Akhmad Rudi Maswanto; Ani Ulyatur Rashida (AL-ASHLAH : Jurnal Hukum Keluarga dan Hukum Islam, 2025)
Parental intervention in the household affairs of their children is a phenomenon that often occurs in society. This study examines parental intervention from the perspective of Islamic law and positive law to determine its legal implications and limits. Using a normative juridical approach, this research analyzes legal sources, including Islamic law principles and national regulations governing family and household matters. The findings indicate that in Islamic law, parental intervention is permissible as long as it aligns with principles of benefit (maslahah) and does not cause harm (mafsadah). Meanwhile, positive law in Indonesia upholds household independence while still recognizing the advisory role of parents. However, excessive intervention that disrupts household harmony may have legal consequences. This study concludes that parental intervention should be conducted wisely, respecting the autonomy of the child's household while providing guidance in accordance with legal and ethical principles.